Organic Agriculture Towards Sustainability - Pilipavicius, Vytautas (IntechOpen, 2014)
Organic agriculture combines tradition, innovation and science to benefit the shared environment and promotes fair relationships and a good quality of life. This book is a compilation of 11 chapters focused on development of organic agriculture, the role of sustainability in ecosystem and social community, analysis of environmental impacts of the organic farming system and its comparison with the conventional one, crop growing and weed control technologies, organic production, effective microorganisms technology. Continuously, a wide range of research experiments focus on organic agriculture technologies, quality of production, environmental protection and non-chemical, ecologically acceptable alternative solutions. In the book Organic Agriculture Towards Sustainability, contributing researchers cover multiple topics respecting modern, precious organic agriculture research.